EVALUASI KEBIJAKAN UANG KULIAH TUNGGAL (UKT) DI UNIVERSITAS RIAU TAHUN 2018 (STUDI KASUS FAKULTAS ILMU SOSIAL DAN ILMU POLITIK) - Bayudi, Halbet; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by the still problems that arise in the implementation of the Single Tuition Policy (UKT) in the Faculty of Social and Political Sciences (FISIP) University of Riau. The purpose of this study is to evaluate the implementation of the Single Tuition Policy (UKT) at the Faculty of Social and Political Sciences, University of Riau in 2018. The research method used is descriptive method with a qualitative approach. Informants were determined by purposive method. The technique of collecting data uses observation, interviews and documentation. The results of the study indicate that effectiveness, adequacy, responsiveness and accuracy in implementing the policy have been fulfilled. Whereas for efficiency and equity not yet fully fulfilled. Keywords: evaluation, single tuition